Soil contamination near non-ferrous metal smelters: A review - Ettler, Vojtěch (Applied geochemistry, 2016)
This review summarizes over 160 studies focused on soil contamination near non-ferrous metal smelters. The methods of these investigations were examined with an emphasis on the combinations of traditional (geo)chemical approaches with various mineralogical and metal isotope techniques that are particularly helpful for depicting the fate of smelter-derived contamination in the soil. Differences in the distributions and binding of metal(loid)s in smelter-affected soils from temperate and (sub)tropical climatic zones indicate the greater vulnerability of the latter. Prevailing wind direction is a key factor affecting the dispersion of smelter emissions and their subsequent deposition into the soils, with greater importance found especially in arid areas. Whereas the greatest contamination is generally observed in the surface soil layers, downward migration of metal(loid)s in the soil profiles has been documented at numerous sites. Contamination of smelter soils significantly affects both plants and soil organisms, but suitable remediation techniques (such as chemical stabilization of soils by amendments) can be used for reducing the bioavailability of contaminants. [Display omitted] •High levels of metal(loid)s in topsoils affected by non-ferrous metal smelters.•Contamination hotspots in soils near smelters reflect prevailing wind direction.•Fate of contaminants in soils controlled by the mineralogy of smelter particulates.•Multi-isotope techniques enable tracing the smelter-related contamination in soils.•Remediation techniques reduce contaminant bioavailability from smelter soils.